(untitled) (Bangladesh Journal of Child Health, 2018)
The manifestations of wasp stings are usually benign and localized at the site of stings but susceptible individuals may present with multisystem and potentially fatal complications like hemolytic anaemia, acute renal failure and shock. We report here a child who developed acute kidney injury seven days after multiple wasp stings. The renal functions recovered with supportive management including two sessions of peritoneal dialysis. This case report highlights that management of some of the wasp stings should be done in consultation with centre which has facilities for dialysis. The management of wasp sting should be started as early as possible and when progressive renal failure ensues, intensive dialysis support results in good renal recovery in majority of survivors. Bangladesh J Child Health 2018; VOL 42 (2) :98-101